2020
DOI: 10.13106/jafeb.2020.vol7.no6.221
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Product Risk, Perceived Satisfaction and Purchase Intentions for Online Shopping

Abstract: This research investigates the relationship among product risk, financial risk, security risk, privacy risk, perceived satisfaction, and purchase intention. Validated measurements were identified from a literature review. The measurement model and the conceptual model depicting hypothesized relationships were evaluated based on responses from 306 customers using confirmatory factor analysis and structural equation modeling. The results showed that product risk, financial risk, security risk, and privacy risk i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
1
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 70 publications
5
38
1
12
Order By: Relevance
“…In recent years, there has been a steady increase in the number of online shoppers and online sales [27]. This was accelerated by the spread of COVID-19, which has pushed people to purchase more from online shops [5,6]. Online shopping has advantages over traditional shopping options because it is available anywhere and at any time [28]; it saves time [29]; it offers a wide range of products [30]; and it makes cost saving possible [31].…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been a steady increase in the number of online shoppers and online sales [27]. This was accelerated by the spread of COVID-19, which has pushed people to purchase more from online shops [5,6]. Online shopping has advantages over traditional shopping options because it is available anywhere and at any time [28]; it saves time [29]; it offers a wide range of products [30]; and it makes cost saving possible [31].…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…Due to the government's social distancing regulations, which have resulted in changes in consumer behavior, there are limitations on movement and activities. Based on these regulations, many activities such as selling or purchasing products have moved to online platforms, and many customers use these platforms to meet their daily needs [5,6]. Online shopping is a rapidly evolving industry, as Internet technologies and applications provide customers with more accessible, convenient, and cost-effective ways to find a wider range of products than traditional shopping [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The invariant features are divided into local features and global features. The global features of an image are mainly three types of image color, texture, and shape, and the local features of an image use a part of the image area to extract features [17].…”
Section: Multifeature Image Feature Extraction Technique Formentioning
confidence: 99%
“…Due to the significant impact of satisfaction on many businesses, previous investigations conducted by Tran (2020) in the online shopping service industry and by Jin et al (2016) in the restaurant industry have suggested minimizing perceived risk for customers. High perceived risk can cause a high threat to customers and lower customer's confidence and joy in using the service.…”
Section: Introductionmentioning
confidence: 99%